Peutz-Jeghars’ syndrome, a rare genetic disorder: A case report - Mone, Fabia Hannan; Roy, Kuntal; Hasan, Gazi Zahirul; Roy, Kaushik; Ahamed, Qazi Sazib; Jui, Jannatul Ferdous (Jour Med Resh and Health Sci, 2020)
Abstract: Hamartomatous polyposis syndromes or Peutz-Jeghers syndrome (PJS) is a hereditary autosomal dominant disease characterized by benign hamartomatous polyps and mucocutaneous pigmentation in the digestive tract. It occurs mostly in the small intestine during first decade of life but frequently in the colon and stomach. Only a few cases have been reported in the duodenum1. Polyposis syndromes are common cause of adult intussusceptions, with polyps acting as lead points. Adult intussusceptions are rare and is almost always associated with that lead point2. Although hamartomatous polyps are not pre-malignant, there is an increased risk of gastrointestinal and non-gastrointestinal malignancy, commonly involving the small bowel. Most patients of PJS presents with acute abdomen and diagnosed as intussusceptions, commonly entero-enteric type but colo-colic intussusceptions are rare in Peutz-Jeghers syndrome3. To the best of our knowledge, synchronous colo-colic intussusception association in Peutz-Jeghers syndrome has not been previously reported.